Refleksi Kekerasan dalam Rumah Tangga dalam Cerita Rakyat Bali Tuwung Kuning: Analisis Feminisme - I Nyoman Suaka (Universitas Udayana, 2018)
The purpose of this article is to examine Tuwung Kuning (Yellow Egg Plant) folklore based on the feminist approach. The object of the study is the drama script and performance Tuwung Kuning recording. Data were analysed with hermeneutic method, namely the interpretation of text both written and audiovisual texts. The results of the study show that the manuscripts and theater express the theme of domestic violence. The female character of the story, Tuwung Kuning, is very weak and in an oppressed conditions. The bullying was carried out by the husband and by environmental conditions of a gambler family. The female character was powerless and oppressed by male-based power of patriarchy, even though in a state of old pregnancy, when giving birth and caring for the child. She was threatened, terrorized and killed. This condition is very contrary to the spirit of feminism that fights for gender equality so that the position of women is equal to men. The change in the fate of this female character is not by herself, but by an angel, as a fortune.